2016
DOI: 10.3727/096368915x688614
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tracking of Human Neural Progenitor Cells in the Rat Brain Using Magnetic Resonance Imaging is Not Enhanced by Ferritin Expression

Abstract: Rapid growth in the field of stem cell research has generated a lot of interest in their therapeutic use, especially in the treatment of neurodegenerative diseases. Specifically, human neural progenitor cells (hNPCs), unique in their capability to differentiate into cells of the neural lineage, have been widely investigated due to their ability to survive, thrive, and migrate toward injured tissues. Still, one of the major roadblocks for clinical applicability arises from the inability to monitor these cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…Furthermore, no correlation was observed between MR signal and cell graft survival. All rejected cell grafts retained histologic iron, resulting in a “false positive” indicator of cell survival, which makes drawing conclusions about transplanted cell graft viability from histological iron challenging, as was shown in previous studies . However, it is still possible to use the histological iron as an indicator of graft location because it correlated with graft location confirmed with human nuclear staining.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, no correlation was observed between MR signal and cell graft survival. All rejected cell grafts retained histologic iron, resulting in a “false positive” indicator of cell survival, which makes drawing conclusions about transplanted cell graft viability from histological iron challenging, as was shown in previous studies . However, it is still possible to use the histological iron as an indicator of graft location because it correlated with graft location confirmed with human nuclear staining.…”
Section: Discussionmentioning
confidence: 92%
“…Reporter gene systems have been designed for bioluminescence imaging , optical imaging , positron emission tomography (PET) , and MR imaging (MRI) . Exogenous contrast agents, including radionuclides for PET and superparamagnetic iron oxide nanoparticles (SPIONs) for MRI, have been used to physically label cells prior to transplantation and represent a less invasive alternative to reporter gene systems , . SPIONs are under investigation as a molecular imaging contrast agent for labeling and tracking transplanted cells with MRI , .…”
Section: Introductionmentioning
confidence: 99%
“…Another study using SPIO labelling of hNPCs in vivo, however, found that it was not a viable imaging technique as it could not determine graft rejection in vivo, which is of utmost importance in understanding cell behavior post-transplantation. [146] This highlights the variability in the results of in vitro and in vivo studies, concordant with the known complexity of biological systems.…”
Section: Diagnostic and Therapeutic Applications Of Nanotechnology Inmentioning
confidence: 74%
“…SPIO-based cell tracking agents have a few limitations that have prevented more widespread usage. In vivo , through apoptosis or exocytosis, SPIOs can label tissue or phagocytic cell types resulting in false positive signals not representative of the target cells; in other words, SPIOs lack live cell specificity [8]. In rapidly dividing cell types, the concentration decreases as cells divide, leading to eventual loss of signal which limits longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Even without synchronization, MEs present a significant advantage over traditional contrast agents for in vivo cell tracking. Upon host cell death, conventional SPIOs are often taken up by other cell types, resulting in false positives [8, 26–30], whereas we have found that the signal from magnetotactic bacterial constructs loaded into mammalian cells is more completely and rapidly cleared upon cell death [24]. …”
Section: Introductionmentioning
confidence: 99%